(untitled) (Journal of Scientific Research, 2023)
The depolymerization reaction of nylon-6,6 is carried out by acidic hydrolysis in the presence of various amounts of sodium dodecyl benzene sulfonic acid (SDBS) (0.02 to 0.07 g) surfactant used as a catalyst at 80 °C and at a different time interval (120 to 240 min). The maximum yield was obtained when 0.05 g SDBS was added to the reaction mixture as a catalyst and 180 min. The reaction mixture was neutralized by 5N NaOH, and the hexamethylene diamine obtained was converted into the Dibenzoyl derivative of hexamethylene diamine (DBHMD), which was filtered, dried, and weighed. The yield was found to be 87.14 %. The characterization was done by the melting point determination and FTIR spectra. The information obtained was in accordance with the literature value. This reaction has followed first-order kinetics with a rate constant of reaction 8.31×10-3 min -1. The IR recorded clearly reveals that the product obtained is pure.